Conjugal plasmid transfer in the plant rhizosphere in the One Health context - Riva, Francesco; Dechesne, Arnaud; Eckert, Ester M.; Riva, Valentina; Borin, Sara; Mapelli, Francesca; Smets, Barth F.; Crotti, Elena (Frontiers in Microbiology, 2024)
Horizontal gene transfer of antibiotic resistance genes (ARGs) is one of the primary routes of antimicrobial resistance (AMR) dissemination. In the One Health context, tracking the spread of mobile genetic elements carrying ARGs in agri-food ecosystems is pivotal to understand AMR diffusion and estimate potential risks for human health. So far little attention has been devoted to plant niches, hence the aim of this work was to evaluate conjugal transfer of ARGs to the bacterial community associated with the plant rhizosphere, a hot spot for microbial abundance and activity in soil. Experiments were conducted using the lettuce as model for vegetables eaten raw and a bacterial strain isolated from treated wastewaters. Hence, we simulated a source of AMR determinants that could enter the food chain via plants through irrigation. Among a collection of isolates, we selected the environmental strain Klebsiella variicola EEF15 as ARG donor because of the relevance of Enterobacteriaceae in the AMR context and the One Health framework. The strain was able to colonize the lettuce rhizosphere and to inhabit its leaf endosphere 7 days past bacterial administration. The strain was genetically manipulated and used to track the conjugal transfer of the broad host range plasmid pKJK5 containing a fluorescent marker gene, to the natural rhizosphere microbiome obtained from lettuce plants. Fluorescence stereomicroscopy revealed plasmid transfer at frequency of 10 -3 ; cell sorting allowed the selection of the transconjugants, which were subsequently identified by 16S rRNA gene amplicon sequencing. The conjugation rates and the strain's ability to colonize the plant rhizosphere and leaf endosphere make strain EEF15::lacI q -pLpp-mCherry-gm R with pKJK5::Plac::gfp an interesting candidate to study ARG spread in the agri-food ecosystem. Future studies taking advantage of additional environmental donor strains could allow to obtain a comprehensive snapshot of AMR spread in the One Health context.